Uji Sitotoksik Ekstrak Etanol Daun Bidara (Ziziphus mauritiana) Yang Tumbuh Di Bukittinggi Dan Di Sijunjung Dengan Metode BSLT (Brine shrimp Lethality Test) - rahmayulis; Aulia, Andini; Hilmarni; Ariya Eka, Kusuma (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2026)
Bidara leaves are a plant that can be used as a traditional medicine. Bidara leaves are believed to have properties that can treat mouth ulcers, lower cholesterol levels and even have potential in treating cancer. Bidara leaves contain secondary metabolites, include alkaloids, flavonoids, phenolics, terpenoids, and saponins. This study aims to determine the differences in cytotoxic activity of bidara leaves growing in the Bukittinggi and Sijunjung areas using the Brine Shrimp Lethality Test (BSLT) method. Bidara leaves were extracted by maceration using 96% ethanol solvent, resulting in a thick extract of Bukittinggi bidara leaves of 15.3 g with a yield of 3.82% and a thick extract of Sijunjung bidara leaves of 19 g with a yield of 5.42%. In the cytotoxic test, the concentration of the test solution used was 10 ppm, 100 ppm, 1,000 ppm, and 10,000 ppm. The results of the cytotoxic activity test of Bukittinggi bidara leaves and Sijunjung bidara leaves were known to be very toxic, with different LC50 values, the ethanol extract of Bukittinggi bidara leaves had an LC50 value of 151.35 ppm and the ethanol extract of Sijunjung bidara leaves had an LC50 value 128.82 ppm. From the results of this study, it can be concluded that the ethanol extract of Sijunjung bidara leaves is more toxic than the ethanol extract of Bukittinggi bidara leaves